Les fondateurs Reconstruire la République après le nazisme - Bernier-Monod, Agathe (Sociétés, Espaces, Temps, 2022)
How to re-establish democracy after Nazism? Where to begin in a destroyed, occupied and divided country? What experience to rely on? In 1945, a handful of trained politicians, both men and women, who had survived war and persecution, undertook the rebuilding of institutions. This book traces the path of thirty-four founders of West German democracy, representatives elected to the Reichstag before 1933 and to the Bundestag after 1949. Their experience of the collapse in 1933 and of the Nazi dictatorship turned them into attentive democrats and favoured their commitment after 1945. Their intertwined narratives offer an original interpretation of the tumult of 20th century Germany. They testify to the continuity of the German democratic tradition beyond Nazism. This publication will interest all those who have questions about German political culture, but also about the inherent fragility of democracy.